Exercise echocardiography in valve disease. Issue 4 (16th April 2018) - Ilardi, F.; Sugimoto, T.; Dulgheru, E. R.; Go, Y. Y.; Marchetta, S.; Contu, L.; Lancellotti, P.
Abstract: Evidence supporting the use of exercise echocardiography to identify the true hemodynamic consequences of valvular heart disease (VHD) is progressively accumulating. From a clinical standpoint, the evaluation of VHD limited to resting conditions often underestimates the full clinical impact of the lesion. Exercise echocardiography has proved to be an important clinical tool in the risk stratification and the decision making of patients with VHD. It is very useful in case of discrepancy between symptoms and severity of valve lesion. Moreover, the evaluation of dynamic components of VHD, ventricular function, and exercise capacity provides clinician additive prognostic value that can be really helpful in the management planning of these patients. Abstract : Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/5935971/Activity.aspx